Five-Year Survival of Patients Treated with Minimally Invasive Direct Coronary Artery Bypass (MIDCAB) Compared with the General Swiss Population - Reuthebuch, Oliver; Stein, Alina; Koechlin, Luca; Gahl, Brigitta; Berdajs, Denis; Santer, David; Eckstein, Friedrich (The Thoracic and Cardiovascular Surgeon, 2023)
Background To evaluate the midterm follow-up and 5-year survival outcome of the minimally invasive direct coronary artery bypass (MIDCAB) procedure compared with the survival of the general Swiss population.Methods Retrospective study on preoperative data, intraoperative data, and postoperative outcome of patients who underwent MIDCAB surgery between June 2010 and February 2019. To assess validity of this surgical therapy, outcomes were compared with survival data of a gender- and age-matched cohort of the general Swiss population taken from the database of the Swiss Federal Statistical Office.Results A total of 88 patients were included. Median (interquartile range [IQR[) age was 66 (56–75) years, and 27% (n = 24) were female. The median (IQR) length of the in-hospital stay was 7 (6–8) days. No postoperative stroke occurred. The 30-day mortality was 1.1% (n = 1). Reintervention for failed left internal mammary artery was needed in 1.1% (n = 1). The median (IQR) ejection fraction was 58% (47–60) preoperatively and remained stable during follow-up. The median (IQR) follow-up period was 3 (1.1–5.2) years. Five years postoperatively, 83% (confidence interval, 69–91) of the patients were alive, showing an overlap with the range of survival of the matched subcohort of the general Swiss population (range, 84–100%).Conclusion Though suffering from coronary heart disease, patients after MIDCAB show almost equal survival rates as an equivalent subcohort corresponding to the general Swiss population matched on age and gender. Thus, our data show this treatment to be safe and beneficial.
Keywords: minimally invasive direct coronary artery bypass; left internal mammary artery; left anterior descending artery; cardiac surgery; off-pump; coronary heart disease